Output Voltage Changes in PV Solar Modules after Electrical and Thermal Stresses. Experimental Analysis. (January 2019) - Zaraket, Jean; Aillerie, Michel; Salame, Chafic; Losson, Etienne
Abstract: Partial shading and dirt areas are the main external reasons inducing via electrical and thermal stresses hot spots in photovoltaic (PV) modules or panels reducing their instantaneous performances and at best their lifetime, at worst a rapid total degradation of the functioning. Even if manufacturers add by-pass diode in the topology of the PV panel, performances of the panel under or after stresses are not taken into consideration in their datasheet which only gives the characteristics under Standard Test Conditions (STC). To test the role of electrical and thermal stresses on the performance of PV module, we performed several series of experimental measurements in the most used commercial modules, i.e. a series of monocrystalline silicon ones. Using a Deep Level Transient Spectroscopy (DLTS) spectrometer based on a double-boxcar system in the post-stress period, this work focusses on the analysis of defects present in stressed PV solar modules for measurements of electrical characteristics of the module. Various reverse currents and temperature levels were applied to induce the stress in dark condition into the solar module structure. The output voltage was measured before and after the applying stress in the same condition for several common periods of time. The changes in efficiency and parameters of PV cells and modules being exposed to shadow effects compared to that in normal working mode are discussed based on output voltage done in the present study.